Farming with Remittances: Female Migration, Agricultural Investment, and Social Mobility in Rural Indramayu, Indonesia - Rani Andriani Budi Kusumo; Iwan Setiawan; Mahra Arari Heryanto; Anne Charina; Gema Wibawa Mukti (Agrisocionomics: Jurnal Sosial Ekonomi Pertanian, 2026)
Low levels of farmer welfare remain prevalent in many agrarian communities. The international migration of women has emerged as a key strategy for farming households to cope with poverty and enhance their livelihoods. This study examines how remittances from female migrant workers are invested in agriculture and assesses their impact on the social mobility of farming households. The research was conducted in Kroya District, Indramayu Regency, a rural and agriculture area with persistently high levels of poverty. This study using a qualitative approach and case study method. The study involved a survey of 50 returnee female migrant, and in-depth interviews with various stakeholders, including village officials, community leaders, and labor brokers. Data were analyzed thematically. The findings show that land is a crucial asset for households of female migrant workers. Accordingly, remittances are primarily used to purchase land, which enhances household food security and elevates their social standing within the village. However, the use of remittances to modernize agricultural production remains limited. This suggests that while remittances strengthen livelihood assets—particularly natural, physical, and social capital—they do not automatically translate into increased agricultural productivity. These findings highlight the need for supportive policies that promote the productive and sustainable use of remittances in agriculture.